2021
DOI: 10.1002/fsn3.2663
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of nutritional and functional qualities of local complementary foods of southern Ethiopia using a customized mixture design

Abstract: Commercially produced complementary foods are inaccessible to rural households in Ethiopia. This study aimed to optimize the nutritional and functional properties of local complementary foods using flours of the following locally available crops: maize, red kidney bean, kocho, and pumpkin fruit. Ten formulations were generated using a customized mixture design. A five‐point hedonic scale was used for the determination of organoleptic properties, and standard methods were used for the analyses of nutritional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
2
5
4
Order By: Relevance
“…This finding was in agreement with the report by Tenagashaw et al ( 49 ) where the protein density of complementary foods from blends of teff, soyabean and orange-fleshed sweet potato was in the range of 3·50–4·79 g/100 kcal. It also agreed with the report by Ayele et al ( 44 ) where the protein density of an optimised formula from kocho, pumpkin fruit, red kidney bean and maize was 3·0 g/100 kcal. Alternatively, the protein density of homemade complementary foods in Wolayita zone of Ethiopia contained lower protein density ranging from 2·13 to 2·48 g/100 kcal as reported by Abeshu et al ( 11 ) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding was in agreement with the report by Tenagashaw et al ( 49 ) where the protein density of complementary foods from blends of teff, soyabean and orange-fleshed sweet potato was in the range of 3·50–4·79 g/100 kcal. It also agreed with the report by Ayele et al ( 44 ) where the protein density of an optimised formula from kocho, pumpkin fruit, red kidney bean and maize was 3·0 g/100 kcal. Alternatively, the protein density of homemade complementary foods in Wolayita zone of Ethiopia contained lower protein density ranging from 2·13 to 2·48 g/100 kcal as reported by Abeshu et al ( 11 ) .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the determined Zn density at 0·68 mg/100 kcal has shown fulfilment for 12–23-month-old children while at a marginal level (61·82 %) when accounted for the requirements for 9–11-month-old children and below the recommended for 6–8-month-old children. The present finding was higher than the Zn density of complementary food at 0·4 mg/100 kcal as reported by Ayele et al ( 44 ) while it was lower than the report by Tenagashaw et al ( 49 ) with a Zn density range of 1·41–1·49 mg/100 kcal.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Crude fiber content was determined by Fibertec 8000, Foss Analytical, Sweden, following official method 978.10, AOAC ( 2016 ). Utilizable carbohydrate was estimated by the difference: 100 − (% Moisture +% Crude protein + % Crude fat + % Crude fiber + % Ash) (Agza et al., 2018 ; Ayele et al., 2021 ). The gross energy (kcal/100 g) of individuals and blended flours was computed based on FAO/WHO ( 1985 ) recently amended 2021 codex guidelines by multiplying the values obtained for energy‐yielding nutrients (crude protein, crude fat, and utilizable carbohydrate) with Atwater conversion factors, where E (kcal/100 g) = [(% crude fat × 9) + (% crude proteins × 4) + (% utilizable carbohydrates × 4)].…”
Section: Methodsmentioning
confidence: 99%